THE INFLUENCE OF COMMUNICATION, PERCEPTION OF ORGANIZATIONAL SUPPORT AND PERSONALITY ON THE TEACHER'S PERFORMANCE AT WORK (An Analyses Study at SMP Negeri 3 Mandor, Landak Regency) - Mujiono (IJGIE (International Journal of Graduate of Islamic Education), 2020)
Background: The influence of a personal and organizational communication support to teachers' working performance is believed to have a high impact to school success achievement. Educational institutions such as high school is a place where teachers are expected to have a clear and effective communication skills in helping students; learning. Interviewing some teachers and document review were conducted to see and understand the validity and realibility of the research questions. Objective: The main aims were to analyze (1) communication, perception of organizational support, personality and performance, (2) communication effect, perception of organizational support and personality toward teacher performance of SMP Negeri 3 Mandor Landak Regency. Method: The population for data completion were the teachers from above school. Data analysis technique used was regression model. Result 1: The results showed that communication variables, perception of organizational support, personality and teacher performance showing regression. Therefore the result 2 showed that the influence of communication, perception of organizational support, personality toward the performance of teachers were significantly good impact with some positive criteria. Conclusion: This analyses study helps to understand how better communication is not just what and how the teachers were supported by the organization but the good communication, achieving and effective support strategies for future teachers are well supported.